2009
DOI: 10.1001/archophthalmol.2009.41
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Slitlamp Optical Coherence Tomography and Scanning Peripheral Anterior Chamber Depth Analyzer to Evaluate Angle Closure in Asian Eyes

Abstract: Objective: To evaluate the effectiveness of slitlamp optical coherence tomography (SL-OCT) and Scanning Peripheral Anterior Chamber depth analyzer (SPAC) in detecting angle closure, using gonioscopy as the reference standard. Methods: A total of 153 subjects underwent gonioscopy, SL-OCT, and SPAC. The anterior chamber angle (ACA) was classified as closed on gonioscopy if the posterior trabecular meshwork could not be seen; with SL-OCT, closure was determined by contact between the iris and angle wall anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
1
6
0
2
Order By: Relevance
“…Our results also imply that the risk for APAC increases from a group of eyes with normal anterior segment measurements to a group of eyes that have moderately shallow anterior chambers and contralateral eyes that have APAC, to a group of eyes with markedly shallow anterior chambers and APAC ( Table 5). The results of our study are also in agreement with recent studies showing that optical coherence tomography is able to image and measure the anterior chamber structure and dimensions in normal eyes and eyes with APAC in subjects of different ethnic background [24][25][26][27][28][29][30]. Interestingly, we found, by OCT measurement, that the anterior chamber angle was closed most often in the nasal quadrant, while, as a corollary, the temporal quadrant was the region least often affected (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…Our results also imply that the risk for APAC increases from a group of eyes with normal anterior segment measurements to a group of eyes that have moderately shallow anterior chambers and contralateral eyes that have APAC, to a group of eyes with markedly shallow anterior chambers and APAC ( Table 5). The results of our study are also in agreement with recent studies showing that optical coherence tomography is able to image and measure the anterior chamber structure and dimensions in normal eyes and eyes with APAC in subjects of different ethnic background [24][25][26][27][28][29][30]. Interestingly, we found, by OCT measurement, that the anterior chamber angle was closed most often in the nasal quadrant, while, as a corollary, the temporal quadrant was the region least often affected (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…Of the 46 eyes with a closed ACA on gonioscopy, AS-OCT detected closed ACA in 76.0% in the temporal and 82.6% in the nasal quadrant. This discrepancy in findings between gonioscopy and AS-OCT was also noted in the study by Wong et al [20]. The explanation for this finding might include differences in the methods of assessing and interpreting the ACA configuration with different techniques.…”
Section: Discussionmentioning
confidence: 58%
“…Nolan et al suggested the possible causes for discrepancy between gonioscopy and AS-OCT were different lighting conditions and distortion of the anterior segment by gonioscopy. They also pointed out different landmarks to define angle closure using the 2 methods [20]. Sakata et al also reported that steep iris profile or short irido-angle contact may explain the different percentage of angle closure between AS OCT and gonioscopy [22].…”
Section: Discussionmentioning
confidence: 99%
“…Wirbelauer et al 4 similarly reported a high sensitivity and specificity (86% and 95%, respectively) for ACA measured with the Visante AS-OCT to detect occludable angles in a German clinic-based population. Interestingly, studies conducted in East Asia based on qualitative assessment of AS-OCT images for contact between the peripheral iris and any part of the angle wall anterior to the scleral spur, found equivalently high sensitivities, 5,[34][35][36][37] but reported specificities as low as 51%, 35 55%, 5 and 58%. 36 It is unclear whether these low specificities reflect differences in definitions of narrow quadrants using AS-OCT and gonioscopy, or if angle closure is being missed by gonioscopy in these populations.…”
Section: Discussionmentioning
confidence: 99%